The light chain IgLV3-21 defines a new poor prognostic subgroup in chronic lymphocytic leukemia: Results of a multicenter study - Stamatopoulos, B; Smith, T; Crompot, E; Pieters, K; Clifford, R; Mraz, M; Robbe, P; Burns, A; Timbs, A; Bruce, D; Hillmen, P; Meuleman, N; et al. (American Association for Cancer Research, 2018)
Purpose: Unmutated (UM) immunoglobulin heavy chain variable region (IgHV) status or IgHV3-21 gene usage is associated with poor prognosis in chronic lymphocytic leukemia (CLL) patients. Interestingly, IgHV3-21 is often co-expressed with light chain IgLV3-21, which is potentially able to trigger cell-autonomous BCR-mediated signaling. However, this light chain has never been characterized independently of the heavy chain IgHV3-21. Experimental Design: We performed total RNA sequencing in 32 patients and investigated IgLV3-21 prognostic impact in terms of treatment-free survival (TFS) and overall survival (OS) in 3 other independent cohorts for a total of 813 patients. IgLV3-21 presence was tested by real-time PCR and confirmed by Sanger sequencing. Results: Using total RNA sequencing to characterize 32 patients with high-risk CLL, we found a high frequency (28%) of IgLV3-21 rearrangements. Gene set enrichment analysis revealed that these patients express higher levels of genes responsible for ribosome biogenesis and translation initiation (P ≺ 0.0001) as well as MYC target genes (P = 0.0003). Patients with IgLV3-21 rearrangements displayed a significantly shorter TFS and OS (P ≺ 0.05), particularly those with IgHV mutation. In each of the three independent validation cohorts, we showed that IgLV3-21 rearrangements—similar to UM IgHV status—conferred poor prognosis compared with mutated IgHV (P ≺ 0.0001). Importantly, we confirmed by multivariate analysis that this was independent of IgHV mutational status or subset #2 stereotyped receptor (P ≺ 0.0001). Conclusions: We have demonstrated for the first time that a light chain can affect CLL prognosis and that IgLV3-21 light chain usage defines a new subgroup of CLL patients with poor prognosis.